2020
DOI: 10.1111/all.14369
|View full text |Cite
|
Sign up to set email alerts
|

Allergy and asthma in children and adolescents during the COVID outbreak: What we know and how we could prevent allergy and asthma flares

Abstract: Additional supporting information may be found online in the Supporting Information section. Allergy and asthma in children and adolescents during the COVID outbreak: What we know and how we could prevent allergy and asthma flaresTo the Editor, The coronavirus disease 2019 (COVID-19) pandemic is affecting people at any age with a more severe course in patients with chronic diseases or comorbidities, men, and elderly patients. The Centers for Disease Control and Prevention (CDC) initially proposed that patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
1
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(107 citation statements)
references
References 11 publications
(23 reference statements)
2
99
1
5
Order By: Relevance
“…While wearing a mask may create a subjective sensation of breathlessness, there is no evidence that wearing a face mask exacerbates any underlying lung condition including asthma 57 . The CDC recommends for everyone, but in particular children/adolescents with chronic diseases, measures of disease prevention including regular hand washing (with soap and water or alcohol‐based sanitizer), avoidance of people who are sick, physical distancing, avoidance of travel, and regular cleaning/disinfection of high‐touch surfaces 6 …”
Section: Implications For Asthma Managementmentioning
confidence: 99%
“…While wearing a mask may create a subjective sensation of breathlessness, there is no evidence that wearing a face mask exacerbates any underlying lung condition including asthma 57 . The CDC recommends for everyone, but in particular children/adolescents with chronic diseases, measures of disease prevention including regular hand washing (with soap and water or alcohol‐based sanitizer), avoidance of people who are sick, physical distancing, avoidance of travel, and regular cleaning/disinfection of high‐touch surfaces 6 …”
Section: Implications For Asthma Managementmentioning
confidence: 99%
“…Two studies that have analysed the prevalence of asthma in two cohorts of COVID‐19 patients in Wuhan, China have established such prevalence in 0−0·9% 41,45 . These results were further confirmed in study populations from other countries 46 . However, recent data from a large cohort of patients in the USA demonstrated that asthma was significantly linked to a longer duration of intubation in patients with COVID‐19 younger than 65 years 47 .…”
Section: The Clinical Association Between Respiratory Viral Infectionmentioning
confidence: 80%
“…Therefore, COVID-19 seems to affect childhood and adolescence scarcely, as very recently demonstrated in Italy [88]. However, allergic and immunodeficient children and adolescents need adequate care in this period.…”
Section: Discussionmentioning
confidence: 94%